Contract Farming and Strategies to link with Farmer Producer Organizations (FPOs): A Review - Chadda, Akshita; Chadda, C. Madhu Latha; Chadda, B.N. Priyanka (Journal of Agricultural Extension Management, 2022)
Agriculture's share in GDP has been dropping in several countries, however, the sector continues to play a major role in many developing country economies. Due to a strong reliance on subsistence farming, with limited technology and inadequate market access, most agricultural production in developing nations is associated with low productivity and low profitability. Contract farming is thought to increase productivity and income through facilitating coordination between farmers and other actors in terms of production, processing and marketing of agricultural products. Contract farming is defined as a company financing "inputs" such as seed, fertiliser, credit, or extension to a farmer in exchange for exclusive purchasing rights over a specific crop. It is a type of vertical integration used in agricultural commodity chains to provide the company more control over the manufacturing process and the end product. Contract farming is receiving a lot of interest from academics and policymakers and is frequently linked to an increase in household income for participants. FPO is a generic term for farmer-producer organizations that are incorporated or registered under the Companies Act, Part IXA, or the Cooperative Societies Act of the respective state. Linking contract farming with FPO can help farmers to increase their income and life style.